Chemotaxonomic Investigation of Cotylelobium Species (Dipterocarpaceae) using Flavonoid Analysis - Joshi, Kunjani (Scientific World, 2010)
During the chemotaxonomic investigation of Dipterocarpaceae, three flavonoid aglycones : flavonol quercetin, flavonol kaempferol and flavone apigenin and four glycosides : Quercetin 3-glucoside, apigenin 5- glucoside, kaempferol 3,5- glucoside and quercetin 3-rutinoside were isolated from the leaves of two species of Cotylelobium (C. lewisianum, and C. scabriusculum). The isolated flavonoids can be used as chemotaxonomic markers. Myricetin, luteolin and proanthocyanidins were not decteted in this investigation. Both the species of Cotylelobium can be regarded as advanced in flavonoid patterns because of the absence of myricetin and loss of proanthocyanidins. The data of the flavonoid patterns and the outcome of cluster analysis are taxonomically useful to resolve the controversies over the systematic arrangement of the species and also suggest the need for a revision of classification of the genus Cotylelobium. Key words: Dipterocarpaceae; Flavones. Flavonols; Chemotaxonomy; Cluster analysis. DOI: 10.3126/sw.v6i6.2629 Scientific World, Vol. 6, No. 6, July 2008 24-26